Identification of viable theoretical (psycho-pedagogical and theological) landmarks for a religious education anchored in contemporaneity - Petrov, George Daniel; Ghiuță, Ștefan Adrian (Technium Social Sciences Journal, 2022)
The beauty of Romanian spirituality is the result of the unity between school and Church, of their collaboration in time, both having the same source - the Savior Jesus Christ, and the same fundamental teaching - His Gospel. We currently feel the influence of a world in full process of secularization, and which deeply affects the Romanian school, which tends distance itself from the Church, being pushed towards an autonomy from God. But a school that excludes God, cannot shape Christian lives. It can facilitate their access to the most modern pedagogical methods and tools, to help them specialize in various fields of science, it can provide optimal conditions for them to stand out, but without God there is a risk of becoming humans without strong roots and without a clear direction. If through science and technology man has over time gained power and control over the outside world, in the absence of God he will remain powerless when having to face inner problems. Therefore, if he turns away from the Church and Christ, the school will no longer be in the service of good, beauty, truth, because only inside our savior Jesus Christ one can find the basis of identifying these values, He is being the supreme reason that was imprinted in His creation, and only through Him will the world be able to aspire to the Absolute. The contemporary society must be open to the process of institutionalized religious education, education that contributes to the full formation of man, to responsibly involving him in active life and in the social side, also legitimized by the guarantee of an integral general culture, as a mandatory component part of the civic and solidarity behavior.